China’s corporate tax management and its economic consequences / Zhang Chen - Zhang , Chen (2017)
Since economic reforms began in 1978, China’s enterprises have undergone considerable changes. So too have the taxation system have experienced major reforms over the last three decades to closely resemble those of the market economies, which included the introduction of corporate income taxes in the country. Since corporate tax is a significant cost to enterprises, firms have introduced corporate tax management to strengthen financial decision-making. The extant theories on corporate tax management have not always been consistent, which is more so with the empirical evidence from China given its unique transition from a socialist structure to one where the market have gradually increased its role in the economy. Given the complexity of the economy and still paramount role of the state in the economy there are still loopholes that corporations often exploit to their advantage, which may make tax management in Chinese listed companies inefficient and unpredictable. The central objective of this study is to analyze the economic consequences of corporate tax management in China. In doing so, the study posits the following three research questions: firstly, what is the impact of corporate tax management on firm performance and how tax management can help maximize firm value?; secondly, what are the market outcomes of corporate tax management and how does government ownership influence these outcomes?; and thirdly, what is the impact of corruption and marketization on corporate tax management, and how do they affect firm performance? The results show that that corporate tax management has a negative direct impact on firms’ market value, which support the agency theory of tax management. Nevertheless, corporate tax management can promote market value through the indirect improvement of firms’ profitability and growth, which suggests that tax management can help but they need the deployment of a sound and effective corporate governance mechanism. Next, the findings show that corporate tax management has the potential to cause adverse future market outcomes so as to cause stock price crashes, which support the bad news hoarding theory. The evidence shows that state ownership cannot alleviate this crash risk. Indeed, municipal listed state-controlled enterprises are more likely to face future crash risks than other enterprises. Finally, the findings show that corruption affects corporate tax management non-linearly in China, which support the theories of “grabbing hand” and “helping hand”. Moreover, corruption positively affects the performance of corporate tax management. Furthermore, marketization helps to mitigate the impact of corruption on corporate tax management at both phases of the inverted U-shaped curve. Overall, the thesis shows that corporate tax management is an important financial strategy that can be designed to enhance the wealth of shareholders. However, due to agency problems, the real consequences of tax management have remained uncertain. The solution to addressing agency problems is to bolster enterprise management with sound internal corporate governance through effective coordination with external markets and institutional development.